Building and testing a simple setup to investigate the electrical properties of polymer/carbon black composites - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (Composite Structures, 2015)
In this work, a simple experimental setup was built to investigate the electrical properties of polymer/carbon black composites. It was found that the measured experimental data from our setup can be well described by the percolation theory and tunneling conduction. Those results indicate that our device is applicable for electrical resistance measurements. Additionally, based on this device, a method was proposed to investigate the electrical properties of disk-shape samples as a function of the radial position in order to study samples with different shear deformation history. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Electrical properties; Experiment method; Polymer composite; Shear